Read African news in Courrier International. - (:unkn) unknown (My University, 2025)
The years 1990 to 2005 were pivotal. After thirty years of independence, Africa was suffering the horrors of the economic adjustments proposed by international institutions. The political regimes in place were at the end of their tether. The military had gradually driven civilians out of the presidential palaces. State power is attractive. People are looking for providential men. Behind the scenes, the former colonial power is plotting to maintain its influence in the management of local affairs. Demographics, once an asset, are starting to become a major issue: young Africans need to be given work. The Western press feasts on the misery and failures of African leaders, who are seen, rightly or wrongly, as incompetent and unenlightened tyrants. The African press, despite its meagre resources, offers a different viewpoint, one that Courrier international echoes.Keywords : Africa, written press, democracy, Courrier international, diplomacy, geopolitics
Keywords: African Research